Social capital influence on supply chain integration in the food processing industry in Malaysia / Zurita Mohd Saleh - Mohd Saleh, Zurita (Faculty of Business and Management, Universiti Teknologi MARA, Puncak Alam Campus, 2017)
Supply chain integration has been established as one of the key factors in influencing supply chain effectiveness. In relation to the food processing industry, the need to integrate supply chain initiatives has become more critical as those involved in the food processing and distribution industry are deemed key players whose roles are pertinent in determining supply chain success. Drawing upon the importance of integration, this study establishes the link between supply chain social capital constructs with integration. Based on a final sample size of 184 food manufacturers, a survey was conducted to determine the influence of supply chain relational capital, supply chain structural and supply chain cognitive on the integration of the food processing supply chain. The findings reveal that all three dimensions of supply chain social capital exert significant influence on supply chain integration, thus indicating the importance and relevance of integration among members in the food processing industry. With such findings, the study establishes that both structural and relational elements are of significant importance in ensuring the achievement of ultimate business performance. Although the study has not directly relate supply chain integration with business performance, the direction of the study is substantial to postulate that such relationships is possible and this therefore will be the direction of future study.